Promoting Policy, Systems, and Environment Change to Prevent Chronic Disease: Lessons Learned From the King County Communities Putting Prevention to Work Initiative. Issue 4 (July 2016) - Cheadle, Allen; Cromp, DeAnn; Krieger, James W.; Chan, Nadine; McNees, Molly; Ross-Viles, Sarah; Kellogg, Ryan; Rahimian, Afsaneh; MacDougall, Erin
Abstract : Context: Initiatives that convene community stakeholders to implement policy, systems, environment, and infrastructure (PSEI) change have become a standard approach for promoting community health. Objective: To assess the PSEI changes brought about by the King County, Washington, Communities Putting Prevention to Work initiative and describe how initiative structures and processes contributed to making changes. Design: The impact evaluation used a logic model design, linking PSEI changes to longer-term behavioral impacts in healthy eating active living and tobacco use and exposure. Qualitative methods, including stakeholder interviews and surveys, were used to identify initiative success factors. Setting: Communities Putting Prevention to Work activities occurred throughout King County, with a focus on 7 low-income communities in South Seattle/King County. Participants: The focus communities had a combined population of 652 000, or 35% of the county total, with lower incomes and higher rates of physical inactivity, tobacco use, poor diet, and chronic disease. Intervention: Twenty-four PSEI strategies were pursued by organizations in sectors including schools, local governments, and community organizations, supported by the public health department. There were 17 healthy eating active living strategies (eg, enhancements to school menus, city planning policies) and 7 tobacco strategies (eg, smoke-free policies in schools, housing, and hospitals). Main Outcome Measure: PSEI changes made and numbers of residents reached. Results: Twenty-two of the 24 strategies achieved significant progress toward implementing PSEI changes. The most common success factor was a "dyad" consisting of a dedicated technical assistance provider—either an outside consultant or public health department staff—working closely with a champion from the participating organizations to bring about PSEI changes. Conclusions: An initiative structure that creates and supports external consultant/internal organizational champion dyads in key community sectors offers a promising approach that may be adopted by similar community health efforts in the future. Abstract : Supplemental Digital Content is Available in the Text.This article describes the structure, implementation, and outcomes from the King County Communities Putting Prevention to Work initiative and describes how initiative structures and processes contributed to making changes.